First Complete Genome Sequence of Yersinia massiliensis - Thomas, Matthew C. (Genome Announc, 2018)
Using a combination of Illumina paired-end sequencing, Pacific Biosciences RS II sequencing, and OpGen Argus whole-genome optical mapping, we report here the first complete genome sequence of Yersinia massiliensis. The completed genome consists of a 4.99-Mb chromosome, a 121-kb megaplasmid, and a 57-kb plasmid.